Geo-data the world geographical encyclopedia - McCoy, John 1976- (Gale virtual reference library, 2003)
The 3rd edition of this comprehensive resource, now published by Gale, provides entries on the physical geography of every country in the world plus other selected locations. Each entry features a relief map depicting the geography of the location plus detailed text that describes its features, climate and vegetation. Entries are formatted with standardized rubrics to facilitate comparison.